2014
DOI: 10.1111/jace.13019
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Electrical Resistance Change with Mechanical Damage in Woven SiC/SiC Composites: Experiment and Modeling

Abstract: Silicon carbide (SiC) fiber‐reinforced SiC matrix composites are inherently multifunctional materials. In addition to their primary function as a structural material, the electric properties of the SiC/SiC composites could be used for the sensing and monitoring of in situ damage nucleation and evolution. To detect damage and use that information to further predict the useful life of a particular component, it is necessary to establish the relationship between damage and electrical resistance change. Here, two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…A representation of the composite similar to the one proposed in [23] is considered, as a network of cells set out parallel and in series (Fig. 7b), and then adapted to the Cerasep®A40C material considered in the present work.…”
Section: Electro-mechanical Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…A representation of the composite similar to the one proposed in [23] is considered, as a network of cells set out parallel and in series (Fig. 7b), and then adapted to the Cerasep®A40C material considered in the present work.…”
Section: Electro-mechanical Modelmentioning
confidence: 99%
“…The damage mode leading to an increase of the resistance is considered, for these materials, to be fiber breakage, describing the strength of fibers by a Weibull distribution function. Regarding CMCs, an analytical model [23] inspired by previous work on CFRPs has been proposed, accounting for both fiber breakage and matrix cracks. The probability of fracture of a fiber is also described by a Weibull distribution function, and fiber fractures are introduced as ruptures in the analytical resistor network.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental studies of damage mechanisms in melt infiltrated (MI) SiC/SiC composite have relied on electrical resistance change [5], acoustic emission and 2D microscopic observations [6], [7]. These studies revealed that matrix cracks initiate in weft tows and in the matrix-rich regions.…”
Section: Introductionmentioning
confidence: 99%